2021
DOI: 10.1021/acsomega.1c00957
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Derivation of a Prediction Model for CO2 Adsorption by Coal

Abstract: Adsorption characteristics of CO 2 by coal are an important reservoir parameter to determine the CO 2 storage capacity of the coal seam. The Langmuir isotherm adsorption model is commonly used to describe the isothermal adsorption line of coal. However, we cannot predict the CO 2 adsorption capacity at other temperatures by using the Langmuir model based on the experimental data at a fixed temperature. This paper analyzes the ε−V ad adsorption characteristic curves of three coal samples over a range of tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…In the same coal-CO 2 system, the CO 2 adsorption characteristic curves of coal at different temperatures are almost on the same curve, indicating that the CO 2 gas adsorption characteristic curve is not affected by temperature, the intermolecular force is the dispersion force, and the adsorption process is physical adsorption. The literature 28,29 found that there is a negative correlation between the adsorption potential and the adsorption space through the analysis of experimental data, which was not affected by the temperature of the sample. Therefore, in the same adsorption system, the adsorption characteristic curve of coal for CO 2 is generally not affected by temperature.…”
Section: Co 2 Adsorption Characteristic Curve the Adsorption Characte...mentioning
confidence: 99%
“…In the same coal-CO 2 system, the CO 2 adsorption characteristic curves of coal at different temperatures are almost on the same curve, indicating that the CO 2 gas adsorption characteristic curve is not affected by temperature, the intermolecular force is the dispersion force, and the adsorption process is physical adsorption. The literature 28,29 found that there is a negative correlation between the adsorption potential and the adsorption space through the analysis of experimental data, which was not affected by the temperature of the sample. Therefore, in the same adsorption system, the adsorption characteristic curve of coal for CO 2 is generally not affected by temperature.…”
Section: Co 2 Adsorption Characteristic Curve the Adsorption Characte...mentioning
confidence: 99%
“…Many researchers have studied the mechanism of CH 4 stimulation by gas injection. Huo et al observed that the increase in CO 2 injection pressure increases the CH 4 recovery and CO 2 storage rates. Sun et al divided the enhanced production process into three stages: initial depressurization, medium-term CO 2 adsorption and replacement, and, finally, the CH 4 and CO 2 coproduction stage.…”
Section: Introductionmentioning
confidence: 99%
“…The temperature significantly impacts coal permeability and further affects the adsorption capacity of the different rank coal samples [19]. In addition, Hao et al indicated that the equilibrium adsorption capacity of CO 2 in coal is logarithmic to pressure and proposed a prediction model of CO 2 adsorption capacity, whose predictions are slightly different from the measured data [20].…”
Section: Introductionmentioning
confidence: 99%